A novel modeling method of friction torque for ball screw based on lubrication performance analysis. (June 2023) - Zhao, Jiajia; Lian, Boyang; Lin, Mingxing; Song, Xianchun; Jiang, Hongkui; Zhang, Daiyan; Qi, Baobao
Ball screw has the advantages of high precision, high efficiency, high stiffness and smooth operation, so it has been widely used in automotive industry, semiconductor, aerospace, medical and other fields. It is significant to research the lubrication theory of ball screw and its influence on friction torque to improve its life. In the complex working conditions of ball screw, the elastohydrodynamic lubrication performance is greatly influenced by the thermal effect, and the lubricating oil will no longer be Newtonian fluid under the coupling action of temperature and pressure. Therefore, a Non-Newtonian thermal elastohydrodynamic lubrication model for ball screw is established and a novel modeling method of friction torque for ball screw is proposed, and the correction of the novel method is verified by experiments.